Assessment of an Automatic Hot Water Sterilizing System-Equipped Dialysis Supply Device's Circuit Degradation, 7 Years Postinstallment. Issue 1 (17th March 2021) - Ogawa, Tomonari; Kanayama, Yuki; Sasaki, Yusuke; Tokui, Kenta; Yasuda, Kunihiko; Hara, Hiroaki; Iwashita, Takatsugu; Shimizu, Taisuke; Hasegawa, Hajime
Abstract : At most dialysis clinics in Japan, a central dialysis fluid delivery system (CDDS) is used primarily to provide consistent treatment to patients. We incorporated hot water disinfection to a CDDS over a 7 year period, after which we assessed the dialysis purification levels. We observed that adequate levels had been maintained. We rated the internal circuits of the device at the 7 year mark, comparing the insides of both the used and unused new Synflex tubing, silicone blades, Teflon tubing, silicone rubber tubing, and stainless steel parts. No bacteria or contamination (such as endotoxins) was detected, and no degradation or damage were observed. Even after the auto-hot water disinfection system was installed, no internal tubing degradation due to hot water or mechanical issues have occurred, and the system's dialysis fluid purification levels have been maintained.